Compensation for volatile elements to modify the microstructure and energy storage performance of (W, Ni)-codoped Na0.5Bi0.5TiO3 ceramic films. Issue 13 (September 2018) - Han, Y.J.; Wang, Y.Z.; Yang, C.H.; Yao, Q.; Chen, J.; Huang, S.F.
Abstract: This work reports the characteristics of nonstoichiometric Na0.5+x Bi0.5+y Ti0.96 W0.01 Ni0.03 O3 (x = 0.0%, y = 1.0%; x = 0.5%, y = 2.0%; x = 1.0%, y = 4.0%) ceramic films derived from chemical solution deposition and the role played by excess Na/Bi in modifying microstructure and electrical properties. Single perovskite phase structure can be maintained in all compositions. Decreased grain size can be obtained with the increasing compensation for volatile Na/Bi elements. Particularly, extra amounts of 0.5 mol% Na and 2.0 mol% Bi leads to reduced leakage and enhanced ferroelectric polarization. Meanwhile, due to the high breakdown electrical field strength and large difference between maximum and remanent polarization, an excellent energy storage performance can be achieved in Na0.505 Bi0.52 Ti0.96 W0.01 Ni0.03 O3 sample, which is distinguished by a recoverable energy storage density of 40.5 J/cm 3 and an energy storage efficiency of 43.6% at 2515 kV/cm as well as a good frequency stability. Hence, the regulation for the content of volatile elements is effective to modify the electrical response of Na0.5 Bi0.5 TiO3 -based materials.